Development of a tool to design AC harmonic filter for HVDC transmission system - Cha, Kwan Hung (2010)
The conversion of power from AC to DC and from DC to AC constitutes the central process of High Voltage Direct Current (HVDC) transmission. Therefore, it is important to real world to understand the principles, which harmonic filters are needed on the HVDC converter station to absorb the harmonics current generated by the HVDC converter. Hence, decrease the impact of the harmonic on the connected AC systems such as AC voltage distortion and telephone interference. Moreover, compensate the demand of the converter station from supply reactive power. The objective of this work is to develop a tool for AC harmonics filter design. This work will implement the technique of designing an AC harmonic filter connected to HVDC converter bus. MATLAB software is used as a simulation tools for this project. This technique capable to perform reliable analysis of studies with fulfilling the filter parameter desired